(untitled) (Stavební obzor - Civil Engineering Journal, 2018)
Based on the basic theory of risk, we add the sensitivity factor in the process of design the risk classification model of the major hazard sources, and establish the quantitative classification model and the qualitative classification three-dimensional model of the major hazard source. According to the risk status of the major hazard sources in the production site, the system of risk evaluation index is determined from the three dimensions of probability, severity and sensitivity. (AHP) was used to calculate the weights of each index, and established the mathematical model of risk classification of major hazard sources in production sites. Besides, there are more than 30 enterprises in Taiwan that were selected for empirical research. The empirical research shows that the risk classification model of the major hazard source which is established in this paper has good practicability and convenience. It is suitable for the government safety supervision department to carry out the hierarchical supervision work, and can systematically and conveniently realize the government’s scientific safety supervision and the effective safety management of the enterprise.